Media representation of South Africas female politicians : the case of the Mail & Guardian – 2010 to 2011 - Phiri, Millie Mayiziveyi (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.